SISTEM INFORMASI AKUNTANSI PERSEDIAAN OBAT DENGAN METODE WEIGHTED AVERAGE UNTUK MENGEFISIENSIKAN BIAYA PEMBELIAN OBAT BERBASIS CLIENT SERVER (STUDI KASUS DIKSP UPTD PUSKESMAS BRANGSONG II) - Ria Rizkiana Ayu Waningrum (STEKOM PRESS, 2018)
In the development of technology and information currently recording inventory is very important for companies, especially those engaged in the distribution of drugs and also inventory information is very important to maintain the health center so that it runs more optimally and also to delay the delivery of drugs from suppliers, this can hamper the service of puskesmas to patients.With this information system, the puskesmas can easily manage previously mixed supplies and use a manual and not yet computerized method which can be very helpful with this program. The focus of the transaction handled is to use the Wegthed Average method is a method used to calculate the value of stock and cost of goods sold to achieve a realistic valuation because the stock is still mixed and still use manual recording. The program will be made web-based as a medium to inform drug supplies, and the expected benefits of making this application are to make it easier for users to get the latest information and get inventory reports in a timely manner and to help control raw materials in order to sanitize inventory and produce more taxes cheap because the value of the final stock is smaller.